Chaosmos Against the Metaphysics of One, or a Defence Against Badiou’s Criticism on Deleuze - Özer, Zülfükar Emir (Elpis Filozófiatudományi Folyóirat, 2018)
Alain Badiou asserts that Deleuze’s philosophy is a reintroduction of the metaphysics of One, although Deleuze tries to overcome it. He thinks that the univocity of Being in Deleuze’s philosophy is a sign of the contingent and coherent cosmos that is the unity of all beings. For Badiou, the reason why Deleuze’s understanding falls back to a metaphysical point is its strong affiliation with Stoic philosophy throughout all his works. Indeed, for Deleuze, Stoicism promises a new understanding that overcomes the opposition between the Presocratics and Platonism. The Stoic concept of lekta – i.e. events-effects – is very prominent according to Deleuze as well. However, Deleuze’s understanding diverges from Stoicism regarding their understanding of cosmos. Deleuze reintroduces the concepts of chaosmos and Nietzsche’s eternal recurrence, by which he overcomes the alleged problems Badiou depicts.